CADRUL EVOLUTIV AL CERERII ŞI OFERTEI PRESEI SCRISE ÎN REPUBLICA MOLDOVA - USM ADMIN (Studia Universitatis Moldaviae: Stiinte Sociale, 2007)
This article reveals the evolutionary frame of the printed press demand and offer. The factors which affect the demand and offer, both of internal media not those of external media, originate in several basic fields: political, economic, social and legislative. The impact and intensity degree of some factors is directly linked to the changes which occur in our society. The research of these factors is very important in diminishing the great disparity between the demand and the offer in the printed press. Also, through this research, a relevant role is played in the enhancement of the printed press impact and effects upon the society.